La lutte internationale contre la piraterie au large de la Somalie depuis 2008 - Alban Sciascia (EchoGéo, 2009)
In few months, Medias has firmly focused on the maritime piracy. At the hands of this increasing interest about this phenomenon, it is advisable to question ourselves on the deep interest which could be the sources of this global struggle against piracy. Basing on a diversified body of knowledge and on an analysis of the powers at play, we will questioning about the deeper motives of the States attendees that allow the deployment of an international coalition of the Somali coast. After having summed up this point, we will take an interest on the implementation, limits and consequences of this cooperation.